Intestinal location- and age-specific variation of intraepithelial T lymphocytes and mucosal microbiota in pigs. (February 2023) - Wiarda, Jayne E.; Watkins, Hannah R.; Gabler, Nicholas K.; Anderson, Christopher L.; Loving, Crystal L.
Abstract: Intraepithelial T lymphocytes (T-IELs) are T cells located within the epithelium that provide a critical line of immune defense in the intestinal tract. In pigs, T-IEL abundances and phenotypes are used to infer putative T-IEL functions and vary by intestinal location and age, though investigations regarding porcine T-IELs are relatively limited. In this study, we expand on analyses of porcine intestinal T-IELs to include additional phenotypic designations not previously recognized in pigs. We describe non-conventional CD8α + CD8β − αβ T-IELs that were most prevalent in the distal intestinal tract and primarily CD16 + CD27 −, a phenotype suggestive of innate-like activation and an activated cell state. Additional T-IEL populations included CD8α + CD8β + αβ, CD2 + CD8α + γδ, and CD2 + CD8α − γδ T-IELs, with increasing proportions of CD16 + CD27 − phenotype in the distal intestine. Thus, putative non-conventional, activated T-IELs were most abundant in the distal intestine within multiple γδ and αβ T-IEL populations. A comparison of T-IEL and respective mucosal microbial community structures across jejunum, ileum, and cecum of 5- and 7-week-old pigs revealed largest community differences were tissue-dependent for both T-IELs and the microbiota. Between 5 and 7 weeks of age, the largest shifts in microbial community compositions occurred in the large intestine, while the largest shifts in T-IEL communities were in the small intestine. Therefore, results indicate different rates of community maturation and stabilization for porcine T-IELs and the mucosal microbiota for proximal versus distal intestinal locations between 5 and 7 weeks of age. Collectively, data emphasize the intestinal tract as a site of location- and age-specific T-IEL and microbial communities that have important implications for understanding intestinal health in pigs. Highlights: Intraepithelial T cell (T-IEL)/microbial communities differ by intestinal location. Largest age-specific shifts in T-IEL compositions occur in the proximal intestine. Largest age-specific shifts in microbial compositions occur in the distal intestine. CD4 − CD8α + CD8β − αβ T cells are a non-conventional, innate-like T-IEL subset in pigs. Non-conventional, activated T-IELs are most abundant in the distal intestine.